ФЕНОМЕНИ ГЛОБАЛІЗМУ ТА АНТИГЛОБАЛІЗМУ В КОНТЕКСТІ ФІЛОСОФСЬКОГО ОСМИСЛЕННЯ МИСТЕЦТВА АВАНГАРДИЗМУ ТА СЮРРЕАЛІЗМУ - Культенко, В. П. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Стаття пропонує аналіз філософських позицій таких апологетів авангардизму тасюрреалізму, як Г. Маркузе, Т. Адорно, В. Беньямін в контексті осмислення можливостей впливукультури на реалії життя людини у сьогоднішньому світі, що перебуває під впливом двохрізноспрямованих рухів – глобалізації та антиглобалізму.Культенко В.П. Феномены глобализма и антизлобализма в контексте философскогоосмысления искусства авангардизма и сюрреализма. Статья предлагает анализ философскихпозиций таких апологетов авангардизма и сюрреализма, как Г. Маркузе, Т. Адорно, В. Беньямин вконтексте осмысления возможностей влияния культуры на реалии жизни человека всегодняшнем мире, который пребывает под воздействием двух разнонаправленных тенденций –глобализации и антиглобализма.Ключевые слова: глобализм, антиглобализм, авангардизм, сюрреализм, культурнаяполитика.Kultenko V.P. Phenomena of globalization and anti globalization at the context ofphilosophical understanding of avangardism and surrealism art. The analysis of philosophicpositions of such apologists of avangardism and surrealism as G. Marcuse, T. Adorno, V. Benjamin isproposed in the article. The analysis is undertaken in the context of understanding of possibilities ofcultural influence on human life in modern world which is under the impact of two opposite tendencies ofglobalization and anti globalization.Keywords: globalization, antiglobalization, avangardism and surrealism art, cultural politic.